2019
DOI: 10.1016/j.jff.2019.05.031
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of gastro-intestinal digestion and colonic biotransformation of curcuminoids considering different formulations and food matrices

Abstract: Pharmaceutical formulations for improving stability and bioavailability of curcuminoids are often produced using excipients unsuitable for food applications. In this work, turmeric oleoresin was microencapsulated by spray drying using gum arabic and maltodextrins to prepare a new ingredient (GA/MD) for food industry. In vitro bioaccessibility and degradation of curcuminoids along the gastro-intestinal tract was investigated, and compared with two commercial ingredients, turmeric powder and Meriva ®. Curcuminoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To date, the human microbial metabolism of quercetin has been thoroughly investigated by identifying a series of phenolic acids that may also be involved in the systemic effect of dietary flavonols [16,17]. however, to our knowledge, the influence of delivery systems on quercetin colonic bioaccessibility, as assessed by human fecal fermentation models, is quite unknown, unlike other functionalized plant extracts [18,19]. Thus, the present study aimed to investigate the human microbial metabolism of quercetin derived from the plant Sophora japonica L., prepared through two different technologies (unformulated and phytosome-formulated).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the human microbial metabolism of quercetin has been thoroughly investigated by identifying a series of phenolic acids that may also be involved in the systemic effect of dietary flavonols [16,17]. however, to our knowledge, the influence of delivery systems on quercetin colonic bioaccessibility, as assessed by human fecal fermentation models, is quite unknown, unlike other functionalized plant extracts [18,19]. Thus, the present study aimed to investigate the human microbial metabolism of quercetin derived from the plant Sophora japonica L., prepared through two different technologies (unformulated and phytosome-formulated).…”
Section: Introductionmentioning
confidence: 99%
“…Cortés-Camargo et al [ 43 ] found that there was a delayed release of lemon essential oil microencapsulated using mesquite gum–chia mucilage mixtures. Papillo et al [ 44 ] reported a high in vitro bioaccessibility of curcuminoids that were microencapsulated using gum arabic and maltodextrins as encapsulating agents. Da Silva Stefani et al [ 45 ] reported a good bioavailability of nanoencapsulated linseed oil using chia seed mucilage as a structuring material.…”
Section: Discussionmentioning
confidence: 99%
“…Curcuminoids are polyphenol compounds derived from turmeric. Among them, curcumin, which is of a bright yellow color, is the principal component [8]. It was expected that with increasing %TRC in the film, more yellowness would be observed.…”
Section: Film Appearance and Colormentioning
confidence: 99%
“…Turmeric (Curcuma longa L.) is a good source of bioactive compounds named curcuminoids, which are mainly yelloworange color. Curcumin, demethoxycurcumin, and bisdemethoxycurcumin are good examples of curcuminoids [8]. Turmeric is now a popular medicinal plant worldwide as it possesses antioxidant, antibacterial, antifungal, antiparasitic, anti-inflammatory, anti-mutagenic and anti-carcinogenic properties [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation